Government-supported and community-based avocado cultivation for livelihood diversification in post-mining communities: A cost-benefit analysis - Mayabella Puspita Nugraha; Herdis Herdiansyah; Ellyna Chairani (Bioculture Journal, 2026)
Background: Agricultural development is increasingly recognized as an important strategy for supporting livelihood transition in regions historically dependent on extractive industries. In Bangka Belitung Province, declining tin mining activities have increased the need for alternative livelihood systems capable of generating economic benefits while maintaining environmental sustainability. Avocado cultivation has emerged as a promising agricultural commodity in Air Belo Village, West Bangka Regency, where plantations are primarily established within production forest areas and former plantation lands. This study evaluates the economic feasibility and examines how governance capacity influences its long-term implementation. Methods: A mixed methods approach combines cost-benefit analysis (CBA) and semi-structured interviews. The analysis uses a 30-year timeframe and a 9% social discount rate. It applies economic net present value (ENPV), economic internal rate of return (EIRR), and benefit-cost ratio (BCR). Governance is measured through four dimensions: actor participation, institutional strength, government support, and market integration, using an organized evaluation framework. Findings: The system is economically feasible. ENPV is IDR 118,551,623, EIRR is 27.98%, and BCR is 1.54. Switch value analysis shows robustness during a 32% price decrease and a 45% cost increase. Greater governance performance is associated with better economic outcomes via reduced transaction costs, improved coordination, and stronger market access. Conclusion: This study demonstrates that governance capacity contributes to the economic viability of avocado cultivation by improving coordination, market access, and institutional support. The findings highlight the importance of strengthening farmer organizations and stakeholder collaboration to support economically sustainable livelihood transition in resource-dependent regions. Novelty/Originality of this article: The originality of this study lies in integrating long-term economic feasibility analysis with a multidimensional governance assessment to explain how institutional capacity shapes the sustainability of livelihood transition in resource-dependent regions.